Informatics in Education and Koli Calling: a Comparative Analysis - SIMON SIMON (Informatics in Education, 2009)
The journal Informatics in Education and the conference Koli Calling are compared, starting with Simon's system for the classification of computing education papers and going on to conduct a brief bibliometric analysis of the authors of papers in both publications, including their repeat rates and the countries from which they come. The analysis finds that despite their different natures, the Lithuanian journal and the Finnish conference are highly comparable in many respects. The broad conclusion is that the two publications work well together - but it would be good to see some Lithuanian authors contributing papers to Koli Calling.